Experimental study of the concrete carbonation - Chinè-Polito, Bruno (2019)
In the construction sector, the concrete and the steel bars represent still the key components, although they are very vulnerable by the atmospheric agents, as in the case of their degradation caused by corrosion. In Costa Rica, due to the absence of effective monitoring methods of civil structures and preventive maintenance actions, predictive model are required to avoid damages to the structure and protect the safety of the users. In this work, we present the results of a study for the carbonation due to the CO2 gas, considering the experimental study of the concrete carbonation without the reinforcing bar. We use an accelerated carbonation chamber under strictly controlled conditions, X ray diffraction and chemical analysis to verify the progress of the carbonation depth in time. The experimental results show the effectiveness of the accelerated carbonation process and give the compression strength of the concrete samples for the different carbonation depth measured in time.